STUDY ON THE CHANGE OF THE INTERNAL WAVE AMPLITUDES IN A DISPLACEMENT PROCESS IN THE VIETNAMESE WATERS - Xuan, Nguyen Ba; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2008)
In  this paper some results  of calculating  and predicting a displacement of the  internal  wave  amplitudes  on  basis  of using the  method of solving  the  equations  of the Eigenvalues and Modes of the internal wave are presented.  The results show that:  the internal waves  always  displace  in  space and time  with  the amplitudes  changed.fi-om  I m to  35m.  The internal waves in  the study region have a tendency of increasing the average amplitudes with the depth and reach the maximum values in the layers of 250m, 350m and 450m.